Analisis Perbandingan Efisiensi Penyaluran Listrik Antara Penghantar ACSR dan ACCC pada Sistem Transmisi 150kV - Oktaria Handayani; Tasdik Darmana; Christine Widyastuti (Energi & Kelistrikan, 2019)
Electricity need in Indonesia continues to increase in accordance with the rate of recovery of the economy and industry and the increase in population. The transmission line transmits electricity from the power plant to the load center via the High Voltage transmission lines (SUTT) or Extra High Voltage Transmissio lines (SUTET), because the long distance causes power losses. The condition before the reconducting of Tebing Tinggi - Kuala Tanjung transmission uses ACSR conductor types and after the reconducting has been replaced by the ACCC, where ACCC has 2 times the current trying of the type of ACSR. In this study, we will examine and analyze the magnitude of the power losses and the efficiency of the distribution of the two types of ACSR and ACCC supply channels with a case study of the 150 kV transmission system Tebing Tinggi - Kuala Tanjung which has a distance of 71.5 km. From the calculation results obtained, after the reconducting process using the conductor the ACCC was able to reduce power losses and increase efficiency by 1.35%.